Musik Klentangan Kutai sebagai Media Sinkretisme dalam Upacara Bekenjong di Desa Bensamar Kabupaten Kutai Kartanegara - Fajriannur, Arief; Gunawan, Asril; Setyoko, Aris (Jurnal Mebang: Kajian Budaya Musik dan Pendidikan Musik, 2024)
Bekenjong is one of the ritual ceremonies that are owned by the people of Kutainese ethnic group in the regency of Kutai Kartanegara. Bekenjong ceremony is functions as a media of traditional medication to pay promises and to prevent disasters, usually accompanied by the Klentangan music ensemble, which is played with the musical instrument Klentangan, Babon Drum, and Gong. Bekenjong in its play cannot be implemented without Klentangan music. Music is an important aspect in Bekenjong, because Klentangan music is a media that connects between Pebelian with the realm of gods. This research uses descriptive qualitative method that covers data collection, observation, and data analysis technique. This research uses Weighted Scale technique by William P, and syncretism concept by Ralph Beals. The results of Bekenjong ceremony research shows that Klentangan music ensemble functioned as a media of syncretism. The process of Bekenjong ceremony then adjusted so that the traditions and customs of the ancestors were able to maintain without any conflicts with social norms or even current beliefs.